Improvement in ventriculomegaly following cervicomedullary decompressive surgery in children with achondroplasia and foramen magnum stenosis. Issue 8 (11th June 2020) - Kashanian, Alon; Chan, Julie; Mukherjee, Debraj; Pressman, Barry D.; Krakow, Deborah; Danielpour, Moise
Abstract: The role of cervicomedullary decompression (CMD) in the care of hydrocephalic achondroplastic children who present with simultaneous foramen magnum stenosis is not well understood. We sought to determine the percentage of symptomatic achondroplastic children with foramen magnum stenosis who had stabilization or improvement in ventriculomegaly following CMD. The authors retrospectively reviewed the records of pediatric patients at Cedars‐Sinai Medical Center with achondroplasia and signs of progressive ventriculomegaly who underwent CMD for symptomatic foramen magnum stenosis between the years 2000 and 2018. Clinical outcomes included changes in fontanelle characteristics, head circumference (HC) percentile, and incidence of ventriculoperitoneal (VP) shunting. Radiographic outcomes measured included changes in Evans ratio. We excluded individuals who were shunted before CMD from our study. Sixteen children presented with symptomatic foramen magnum stenosis and full anterior fontanelle or jump in the HC percentiles. Two children underwent placement of a VP shunt before decompressive surgery and were excluded from further analysis. Of the remaining 14 children who underwent CMD, 13 (93%) showed softening or flattening of their fontanelles post‐operatively. Ten of these 14 children had both pre‐ and post‐operative HC percentile records available, with 8 showing increasing HC percentiles before surgery. Seven of those eight children (88%) showed a deceleration or stabilization of HC growth velocity following decompression of the foramen magnum. Among 10 children with available pre‐ and post‐operative brain imaging, ventricular size improved in 5 (50%), stabilized in 2 (20%), and slightly increased in 3 (30%) children after decompression. Two children (14%) required a shunt despite decompression of the foramen magnum. A significant proportion of children with concomitant signs of raised intracranial pressure or findings of progressive ventriculomegaly and foramen magnum stenosis may have improvement or stabilization of these findings following CMD. CMD may decrease the need for VP shunting and its associated complications in the select group of hydrocephalic children with achondroplasia presenting with symptomatic foramen magnum stenosis.